2014
DOI: 10.3109/01942638.2014.904470
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Inclusion in Play among Children with Physical Disabilities in Childcare Centers: An Integrative Review

Abstract: The purpose of this integrative review was to examine strategies that facilitate inclusion in play among children with physical disabilities in childcare centers. Nine databases were systematically searched for peer reviewed empirical studies investigating inclusion strategies for play in childcare settings among preschoolers with physical disabilities. Nine studies met the inclusion criteria and were appraised using the McMaster Critical Review Forms. The inclusion approaches identified were grouped into rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…The environment should be adapted for the assistive devices or the assistive device should be adapted to the environment. Creating an enabling environment is according to Crawford, Stafford, Phillips, Scott, and Tucker (2014) one of the main strategies within habilitation to promote participation in play. Other equally important strategies were toys that promoted cooperative play, a facilitating adult and the need to work client-centred (Frey & Kaiser, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The environment should be adapted for the assistive devices or the assistive device should be adapted to the environment. Creating an enabling environment is according to Crawford, Stafford, Phillips, Scott, and Tucker (2014) one of the main strategies within habilitation to promote participation in play. Other equally important strategies were toys that promoted cooperative play, a facilitating adult and the need to work client-centred (Frey & Kaiser, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similar types of responsive caregiving behavior have been found effective for facilitating peer interactions of young children with and without disabilities or delays [132,308,335]. Bowman et al [332], for example, found in their review of preschool teachers use of responsive caregiving practices that responsive caregiving was among a number of teaching strategies that enhanced positive peer interactions.…”
Section: Interactional Practicesmentioning
confidence: 97%
“…The research foundations for the three instructional practices include the effects of different methods and strategies that parents or practitioners use to reinforce child behavior and facilitate acquisition of new competencies; for example, [21,59,63,242,303,[305][306][307]. The research foundations also include evidence for the effects of arranging or manipulating antecedent events as conditions for instructional practices to have optimal benefits [132,308,309]. Nearly all research synthesis investigators concluded that use of the key characteristics of the instructional practices is associated with discernible child benefits [239,300,306,307].…”
Section: Instructional Practicesmentioning
confidence: 99%
“…A more playful child has more internal control, is more intrinsically motivated, is freer from some constraints of reality, and is better able to give and receive interactional cues than a less playful child (Bundy, 1997; Hamm, 2006; Harkness and Bundy, 2001). Although the child with SPID may not be able to independently engage in play opportunities in the immediate environment, considerations such as the arrangement of space (into clearly defined places, without the obstruction of furnishings) and the selection, presentation and adaptation of materials are known to help children orient and engage more effectively with play materials (Crawford et al., 2014). Accommodations regarding noise-levels, lighting and general accessibility also promote more positive play experiences for children of various abilities (Doctoroff, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%